LMD multi-layer and multi-pass laser welding method for L-PBF formed Ti6Al4V titanium alloy filled with TA0 powder
Through multi-layer multi-channel laser powder filling welding technology, TA0 powder is used to weld the L-PBF-formed TC4 titanium alloy, which solves the problem of insufficient plastic toughness of the welded joints, and realizes high-quality welded joints, meeting the needs of engineering applications.
Patent Information
- Application Number
- CN202510161995.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-13
AI Technical Summary
There are thick β columnar crystals and hard and brittle needle-shaped α'martensite in the L-PBF-formed TC4 titanium alloy welded joints, resulting in insufficient plastic toughness of the joints and cannot meet the needs of actual engineering applications.
Multi-layer multi-channel laser powder filling welding technology is used to weld the L-PBF-formed TC4 titanium alloy through TA0 powder. First, pre-welding treatment includes mechanical grinding, chemical cleaning and vacuum drying. Then, using the method of coaxial integration of laser and powder feeding equipment to melt and deposition layer by layer to complete the welding process.
A laser welded joint with good forming and excellent mechanical properties was obtained, which significantly improved the plasticity of the joint and met the needs of actual engineering applications.
Smart Images

Figure HDA0005271305740000011 
Figure HDA0005271305740000012 
Figure HDA0005271305740000013
Abstract
Description
Technical Field
[0001] The invention belongs to the field of titanium alloy laser welding, and specifically relates to a new laser welding method for TC4 titanium alloy filled with TA0 powder formed by laser powder bed fusion (L-PBF). Background Art
[0002] In recent years, with the significant increase in the use of titanium alloys in related industries and the continuous improvement of their application level, the service performance requirements for structural parts have also increased, and the design and manufacture of titanium alloy overall structures have therefore received more and more attention. However, the processing difficulty of some titanium alloy structures containing complex internal flow channels, porous lattices and other features has far exceeded the limits of traditional titanium alloy processing technology. This type of titanium alloy structural part is not only difficult to process the material itself, but its structural complexity also brings additional manufacturing challenges. Laser Powder Bed Fusion (L-PBF), as a mainstream direct additive manufacturing technology for titanium and titanium alloy parts, has shown significant advantages in the forming and manufacturing of complex and precise titanium alloy structural parts with its unique ability to freely manufacture complex parts.
[0003] TC4 titanium alloy is a typical α+β dual-phase titanium alloy, known for its significant advantages such as high specific strength, strong heat resistance and good corrosion resistance. The mechanical properties of TC4 titanium alloy formed by L-PBF technology are superior to those of forged and cast TC4 titanium alloy, so it is widely used in many fields such as aerospace, defense industry, marine engineering, etc.
[0004] However, due to the limited size of the forming chamber of the L-PBF equipment, this technology is difficult to meet the integrated forming requirements of large-sized and complex TC4 titanium alloy structural parts in actual production. In the subsequent production and application links, once the parts are damaged or worn, their mechanical properties will be greatly weakened and their service life will be shortened accordingly. If the damaged parts are directly discarded or replaced, the manufacturing cost will be greatly increased. Therefore, in order to produce large-sized L-PBF-formed TC4 titanium alloy structural parts efficiently, maintainably and at low cost, it is particularly important and necessary to use welding technology to connect L-PBF-formed parts.
[0005] However, the presence of coarse β columnar crystals and hard and brittle needle-shaped α′ martensite in the L-PBF formed TC4 titanium alloy welded joint seriously reduces the plastic toughness of the joint and cannot meet the needs of practical engineering applications.
[0006] Therefore, obtaining L-PBF formed TC4 titanium alloy welded joints with good plasticity becomes a very challenging task. Summary of the invention
[0007] The present invention proposes an improved laser welding method, firstly, the workpiece to be welded is subjected to pre-welding treatment, including mechanical grinding, chemical cleaning and vacuum drying, to ensure the cleanliness of the welding surface. Subsequently, the L-PBF formed TC4 titanium alloy is welded by using multi-layer and multi-pass laser powder filling welding technology with TA0 powder as the filling material. Through this method, a laser welded joint with good forming and excellent mechanical properties is obtained, and high-quality connection of L-PBF formed TC4 alloy is achieved.
[0008] The L-PBF formed TA0 titanium alloy raw material used in the present invention has a particle size of 75-105 μm, wherein the mass fraction of each element is as follows: Al: 0.38% to 0.45%, V: 0.27% to 0.33%, Fe: 0.17% to 0.23%, Ni: ≤0.03%, and the remainder is Ti.
[0009] In order to achieve the above object, the technical solution of the present invention is as follows:
[0010] (1) forming a groove at a butt joint of the L-PBF formed TC4 titanium alloy sheet;
[0011] (2) The base metal after the groove is opened is first mechanically polished, and then the base metal to be welded is chemically cleaned;
[0012] (3) Place the cleaned base metal to be welded in a vacuum drying oven for drying;
[0013] (4) Fix the dried material to be welded on the welding fixture and place it in a protective atmosphere box, passing protective gas;
[0014] (5) Start the fiber laser, use a coaxial powder feeding method to feed metal powder into the weld, and weld the materials to be welded layer by layer through a multi-layer and multi-pass laser welding process.
[0015] Preferably, the groove in step (1) is in the form of a "V"-shaped groove with a single-side angle of 30° and no blunt edge.
[0016] Preferably, the mechanical grinding described in step (2) uses 80-400 mesh sandpaper to grind the groove of the welded part to have a metallic luster.
[0017] Preferably, the chemical cleaning in step (2) is carried out by washing in a 20% (mass percentage) nitric acid + 1-2% hydrofluoric acid aqueous solution for 6-8 minutes, and when the silvery white metal is exposed on the surface of the plate, the plate is taken out and rinsed under running water. Then, the plate is washed with a 20%-25% (mass fraction) sodium hydroxide aqueous solution for 4-6 minutes, and then the plate is rinsed under running water, and finally, it is washed with acetone.
[0017] The vacuum drying described in step (3) is carried out at 80-100°C for 1-2 hours. The time from completion of cleaning to the start of welding must not exceed 4 hours. If it exceeds 4 hours, the cleaning process of the two base material surfaces to be welded needs to be repeated.
[0018] Preferably, the protective gas in step (4) is argon with a purity of 99.99%, and the gas flow rate is controlled at 20-25 L / min.
[0019] Preferably, the filler metal powder described in step (5) is TA0 powder prepared by gas atomization, with a particle size of 75-105 μm, wherein the mass fraction of each element is as follows: Al: 0.38% to 0.45%, V: 0.27% to 0.33%, Fe: 0.17% to 0.23%, Ni: ≤0.03%, and the remainder is Ti.
[0020] Preferably, the multi-layer and multi-pass laser welding process parameters described in step (5) are as follows: the first pass is a base weld, and the corresponding parameters are as follows: laser power 300-400W, spot diameter 2mm, welding speed 0.3-0.5m / min, and powder feeding amount 5.87-7.05g / min; the second to fourth passes are filling welds, and the corresponding parameters are as follows: laser power 1300-1500W, spot diameter 3mm, welding speed 0.3-0.5m / min, and powder feeding amount 7.05-9.40g / min; the fifth pass is a cap weld, and the corresponding parameters are as follows: laser power 1300-1500W, spot diameter 3mm, welding speed 0.3-0.5m / min, and powder feeding amount 7.05g / min.
[0021] The key reason why the present invention can obtain a welded joint with good mechanical properties is that it adopts a multi-layer and multi-pass laser powder filling welding technology. This technology uses a laser beam as a heat source to melt and accumulate TA0 powder layer by layer between the base materials to be welded until the groove is filled and the welding is completed. On the one hand, through the multi-layer and multi-pass accumulation method, the welding heat impact of each pass is equivalent to heat treatment of the lower weld, which helps to regulate the organizational morphology and thus improve the plasticity of the joint. On the other hand, since the martensitic transformation temperature of the TA0 material is much higher than that of the TC4 alloy, the martensitic phase transformation from β→α′ does not occur in the weld during the welding process, thereby effectively avoiding the formation of the hard and brittle α′ martensitic phase. In addition, due to the difference in element content and organization between the weld and the base material, the overheated β grains in the heat-affected zone cannot grow epitaxially to the weld and form coarse β columnar crystals. On the contrary, the organization in the weld is a softer blocky α phase, which does not have obvious anisotropy, so the deformation coordination ability is better. These factors work together to greatly improve the plasticity of the joint.
[0022] The present invention provides a new method for L-PBF forming TC4 titanium alloy multi-layer multi-pass laser powder filling welding, which has the following beneficial effects:
[0023] (1) The present invention adopts a multi-layer and multi-pass laser powder filling welding method, and after optimizing the process parameters, successfully obtains a joint with good forming and excellent mechanical properties.
[0024] (2) The TA0 powder filled in the present invention is transformed into a blocky α phase during the welding process. Compared with the needle-shaped α′ martensite phase in the TC4 alloy, the blocky α phase is softer in texture and has less obvious anisotropy, and has better plastic deformation coordination ability. Therefore, while maintaining a certain strength of the joint, the elongation of the joint is significantly improved.
[0025] Therefore, the LMD multi-layer and multi-pass laser welding method filled with TA0 powder proposed in the present invention is expected to solve the welding problem of L-PBF formed TC4 titanium alloy and promote the widespread application of L-PBF formed titanium alloy components in the actual engineering field. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of multi-layer and multi-pass laser welding of TC4 titanium alloy formed by LPBF.
[0027] Figure 2 The cross-sectional morphologies of LPBF-formed TC4 titanium alloy multi-layer and multi-pass laser welding joints, where (a) is the cross-sectional morphology of the joint in Example 1, (b) is the cross-sectional morphology of the joint in Example 2, and (c) is the cross-sectional morphology of the joint in Comparative Example 1.
[0028] Figure 3 The stress-strain curves of Example 1, Example 2 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0030] Unless otherwise specified, the experimental materials and related equipment involved in the following examples and comparative examples can be obtained through commercial channels.
[0031] Example 1
[0032] This embodiment is a multi-layer and multi-pass laser welding method for L-PBF formed TC4 titanium alloy. The material involved is 50mm*25mm*5mm LPBF formed TC4 titanium alloy, and TA0 powder is filled during the welding process.
[0033] The specific steps are as follows:
[0034] 1. Open a V-shaped groove at the butt joint of the L-PBF-formed TC4 titanium alloy base material to be welded, with a single-side angle of 30° and no blunt edge;
[0035] 2. Mechanically grind the base material after the groove is opened: use 80- and 400-grit sandpaper to grind the oxide film on all surfaces of the base material to be welded until the metallic luster of the aluminum alloy is revealed;
[0036] 3. After mechanical grinding, chemical cleaning is required. Chemical cleaning is to use 20% (mass percentage) nitric acid + 1-2% hydrofluoric acid aqueous solution to clean for 8 minutes. When the silvery white metal is exposed on the surface of the plate, take out the plate and rinse it under running water. Then use 20%-25% (mass fraction) sodium hydroxide aqueous solution to clean for 5 minutes, then rinse the plate under running water, and finally clean it with acetone.
[0037] 4. After chemical cleaning, place the plate to be welded in a vacuum drying oven and dry at 80°C for 2 hours;
[0038] 5. Fix the cleaned and dried workpiece to be welded on the welding fixture, place the two workpieces butt-jointed without leaving any assembly gap, and then place the fixture as a whole into the protective atmosphere box. During this process, make sure that no oil stains are contaminated on the workpiece to be welded;
[0039] 6. Set the laser welding parameters: Pass 1: Laser power 400W, spot diameter 2mm, welding speed 0.5m / min, powder feeding 5.87g / min. Passes 2-4: Laser power 1500W, spot diameter 3.0mm, welding speed 0.5m / min, powder feeding 9.40g / min. Pass 5: Laser power 1500W, spot diameter 3.0mm, welding speed 0.5m / min, powder feeding 7.05g / min.
[0040] 7. The laser and powder feeding equipment are coaxially integrated, and argon gas with a purity of up to 99.99% is introduced as the protective gas. The gas flow rate is controlled at 25L / min. The laser is controlled to emit laser, and the powder feeding device is started to feed powder at the same time. Finally, the robot is controlled to follow Figure 1 The path planning shown in the figure is to melt and deposit layer by layer to complete the welding process. The cross-section of the weld seam of the obtained weld joint is as follows: Figure 2 As shown in (a).
[0041] Example 2
[0042] The present embodiment is a multi-layer and multi-pass laser welding method for L-PBF formed TC4 titanium alloy, the material involved is 50mm*25mm*5mm LPBF formed TC4 titanium alloy, and TC4 powder is filled in the welding process (the particle size of the TC4 titanium alloy raw material powder is 15-53μm, and the content of the main alloy elements is: Al: 5.77%-6.65%, V: 4.12%-4.56%, Fe: 0.255%-0.351%, Cr: 0.194%-0.380%, Ni: 0.136%-0.184%, and the balance is Ti).
[0043] The specific steps are as follows:
[0044] 1. Open a V-shaped groove at the butt joint of the L-PBF-formed TC4 titanium alloy base material to be welded, with a single-side angle of 30° and no blunt edge;
[0045] 2. Mechanically grind the base material after the groove is opened: use 80- and 400-grit sandpaper to grind the oxide film on all surfaces of the base material to be welded until the metallic luster of the aluminum alloy is revealed;
[0046] 3. After mechanical grinding, chemical cleaning is required. Chemical cleaning is to use 20% (mass percentage) nitric acid + 1-2% hydrofluoric acid aqueous solution to clean for 8 minutes. When the silver-white metal is exposed on the surface of the plate, take out the plate and rinse it under running water. Then use 20%-25% (volume fraction) sodium hydroxide aqueous solution to clean for 5 minutes, then rinse the plate under running water, and finally clean it with acetone.
[0047] 4. After chemical cleaning, place the plate to be welded in a vacuum drying oven and dry at 80°C for 2 hours;
[0048] 5. Fix the cleaned and dried workpiece to be welded on the welding fixture, place the two workpieces butt-jointed without leaving any assembly gap, and then place the fixture as a whole into the protective atmosphere box. During this process, make sure that no oil stains are contaminated on the workpiece to be welded;
[0049] 6. Set the laser welding parameters: Pass 1: Laser power 400W, spot diameter 2mm, welding speed 0.5m / min, powder feeding 5.87g / min. Passes 2-4: Laser power 1500W, spot diameter 3.0mm, welding speed 0.5m / min, powder feeding 9.40g / min. Pass 5: Laser power 1500W, spot diameter 3.0mm, welding speed 0.5m / min, powder feeding 7.05g / min.
[0050] 7. The laser and powder feeding equipment are coaxially integrated, and argon gas with a purity of up to 99.99% is introduced as the protective gas. The gas flow rate is controlled at 25L / min. The laser is controlled to emit laser, and the powder feeding device is started to feed powder at the same time. Finally, the robot is controlled to follow Figure 1 The path planning shown in the figure is to melt and deposit layer by layer to complete the welding process. The cross-section of the weld seam of the obtained weld joint is as follows: Figure 2 As shown in (b).
[0051] Comparative Example 1
[0052] This comparative example is a multi-layer and multi-pass laser welding method of L-PBF formed TC4 titanium alloy. The material involved is 50mm*25mm*5mm LPBF formed TC4 titanium alloy, and TC4 powder is filled during the welding process.
[0053] The specific steps are as follows:
[0054] 1. Open a V-shaped groove at the butt joint of the L-PBF-formed TC4 titanium alloy base material to be welded, with a single-side angle of 30° and no blunt edge;
[0055] 2. Mechanically grind the base material after the groove is opened: use 80- and 400-grit sandpaper to grind the oxide film on all surfaces of the base material to be welded until the metallic luster of the aluminum alloy is revealed;
[0056] 3. After mechanical grinding, chemical cleaning is required. Chemical cleaning is to use 20% (mass percentage) nitric acid + 1-2% hydrofluoric acid aqueous solution to clean for 8 minutes. When the silver-white metal is exposed on the surface of the plate, take out the plate and rinse it under running water. Then use 20%-25% (volume fraction) sodium hydroxide aqueous solution to clean for 5 minutes, then rinse the plate under running water, and finally clean it with acetone.
[0057] 4. After chemical cleaning, place the plate to be welded in a vacuum drying oven and dry at 80°C for 2 hours;
[0058] 5. Fix the cleaned and dried workpiece to be welded on the welding fixture, place the two workpieces butt-jointed without leaving any assembly gap, and then place the fixture as a whole into the protective atmosphere box. During this process, make sure that no oil stains are contaminated on the workpiece to be welded;
[0059] 6. Set the laser welding parameters: Pass 1: Laser power 300W, spot diameter 2mm, welding speed 0.3m / min, powder feeding 7.05g / min. Passes 2-4: Laser power 1300W, spot diameter 3.0mm, welding speed 0.3m / min, powder feeding 7.05g / min. Pass 5: Laser power 1300W, spot diameter 3.0mm, welding speed 0.3m / min, powder feeding 7.05g / min
[0060] 7. The laser and powder feeding equipment are coaxially integrated, and argon gas with a purity of up to 99.99% is introduced as the protective gas. The gas flow rate is controlled at 25L / min. The laser is controlled to emit laser, and the powder feeding device is started to feed powder at the same time. Finally, the robot is controlled to follow Figure 1 The path planning shown in the figure is to melt and deposit layer by layer to complete the welding process. The cross-section of the weld seam of the obtained weld joint is as follows: Figure 2 As shown in (c).
[0061] Through the parameters in Table 1 and Figure 2 Comparison of the cross-sectional morphology of each joint shows that after optimization of the welding process parameters, the joint strength increased from 872MPa to 1030MPa, and the elongation increased from 2.1% to 3.2%. Using the optimized welding process parameters, the plasticity of the welded joint filled with TA0 powder was greatly improved to 8.5%. It can be seen that the weld structure was improved by filling TA0 powder, thereby achieving a significant improvement in the plasticity of the L-PBF formed TC4 titanium alloy welded joint.
[0062] Table 1 Mechanical property values obtained by using the GBT 2651-2008 weld joint tensile test method for Examples 1 and 2 and Comparative Example 1. Table 1
[0063] name Tensile strength(MPa) Elongation after break (%) Example 1 593 8.5 Example 2 1030 3.2 Comparative Example 1 872 2.1 .
Claims
1. A L-PBF formed Ti6Al4V titanium alloy filled with TA0 powder LMD multi-layer multi-pass laser welding method, characterized in that: The following steps are involved: (1) forming a groove at a butt joint of the L-PBF formed TC4 titanium alloy sheet; (2) The base metal after the groove is opened is first mechanically polished, and then the base metal to be welded is chemically cleaned; (3) Place the cleaned base metal to be welded in a vacuum drying oven for drying; (4) Fix the dried material to be welded on the welding fixture and place it in a protective atmosphere box, passing protective gas; (5) Start the fiber laser, use a coaxial powder feeding method to feed metal powder into the weld, and weld the materials to be welded layer by layer through a multi-layer and multi-pass laser welding process.
2. The method according to claim 1, characterized in that The groove described in step (1) is in the form of a "V"-shaped groove, with a single-side angle of 30° and no blunt edge.
3. The method according to claim 1, characterized in that The mechanical grinding described in step (2) uses 80-400 mesh sandpaper to grind the groove of the welded part to have a metallic luster.
4. The method according to claim 1, characterized in that The chemical cleaning described in step (2) is carried out by washing in a 20% (mass percentage) nitric acid + 1-2% hydrofluoric acid aqueous solution for 6-8 minutes. When the silvery white metal is exposed on the surface of the plate, the plate is taken out and rinsed under running water; then washed with a 20%-25% (mass fraction) sodium hydroxide aqueous solution for 4-6 minutes, then rinsed under running water, and finally washed with acetone.
5. The method according to claim 1, characterized in that The vacuum drying described in step (3) is carried out at 80-100°C for 1-2 hours. The time from completion of cleaning to the start of welding must not exceed 4 hours. If it exceeds 4 hours, the cleaning process of the two base material surfaces to be welded needs to be repeated.
6. The method according to claim 1, characterized in that The protective gas described in step (4) is argon gas with a purity of 99.99%, and the gas flow rate is controlled at 20-25 L / min.
7. The method according to claim 1, characterized in that The filler metal powder described in step (5) is TA0 powder prepared by gas atomization, with a particle size of 75-105μm, wherein the mass fraction of each element is as follows: Al: 0.38%~0.45%, V: 0.27%~0.33%, Fe: 0.17%~0.23%, Ni: ≤0.03%, and the balance is Ti.
8. The method according to claim 1, characterized in that The multi-layer and multi-pass laser welding process parameters described in step (5) are as follows: the first pass is a base weld, and the corresponding parameters are as follows: laser power 300-400W, spot diameter 2mm, welding speed 0.3-0.5m / min, and powder feeding amount 5.87-7.05g / min; the second to fourth passes are filling welds, and the corresponding parameters are as follows: laser power 1300-1500W, spot diameter 3mm, welding speed 0.3-0.5m / min, and powder feeding amount 7.05-9.40g / min; the fifth pass is a cap weld, and the corresponding parameters are as follows: laser power 1300-1500W, spot diameter 3mm, welding speed 0.3-0.5m / min, and powder feeding amount 7.05g / min.
9. A welded part prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Gas protection device and method for large-thickness metal part by laser welding
CN110102883A
Control method for eliminating weld crack of high temperature titanium alloy plate
CN110860792A
Self-shielded flux-cored wire suitable for welding of TC4 titanium alloy
CN111745268A
Laser welding method for melt forming of AlSi10Mg alloy / 6061 aluminum alloy through laser powder bed
CN117943688A
Titanium alloy welding wire capable of adjusting strength and toughness of joint and preparation method of titanium alloy welding wire
CN118951488A
Cited By
Composite connection method for thick plate titanium alloy and thick plate titanium alloy structural part
CN121820895A
Composite connecting method of thick plate titanium alloy, thick plate titanium alloy structural member
CN121820895B